Analysis of Online Learning From the Aspect of Learning Interest of Class V Elementary School: Analisis Pembelajaran Daring Ditinjau dari Aspek Minat Belajar Siswa Kelas V SD - Muhamad Soleh; Tri Linggo Wati (Academia Open, 2021)
This study aims to determine online learning in terms of the learning interest aspect of fifth graders at SDN Sawocangkring. The study used the Narrative qualitative method with three research subjects selected by the researcher, while the subject selection was based on the uniqueness of the subject who was deemed able to answer the existing problems. The research instrument consisted of interviews, observation and documentation. Test the validity of the data using triangulation techniques. And data analysis techniques using data reduction, data presentation, and drawing conclusions. Based on the results of research that has been done, the application of online learning so far is still not optimal, seen from the facilities and infrastructure as well as the monotonous learning process. The three subjects have low interest in learning. This is because when following the learning process students pay less attention to ongoing learning activities. The conclusion of this study is that of the three subjects studied, students have low interest in learning, it is said to be low if students do not meet one of the indicators of interest in learning. Namely students pay less attention when learning takes place.